The Dynamics of Contagion and Behavior of the Euro Area Sovereign Bond Markets - Kchaou, Oussama; Salim BEN SASSI; Makram BELLALAH (Bankers, Markets & Investors, 2022)
We investigate the contagion dynamics in the main Economic and Monetary Union sovereign bond markets during the subprime and euro crises. To this end, we adopt the APARCH-ADCC model and the Markov Switching Dynamic Regression model. The impact of both crises on each country in our sample is investigated using two crisis indicators: synchronization and intensity. The empirical results show that contagious episodes and their intensities vary over time and across market pairs for both crises, thus illustrating the complexity of this phenomenon. They also reveal that the market couples composed of the Economic and Monetary Union peripheral countries were immune to the contagion of the subprime crisis and that its third phase was the most violent in terms of the intensity of the transmission of shocks. Moreover, the results show that all the countries in our sample were affected by contagion from the euro crisis, at least during one of its sub-phases. Furthermore, before the first rescue plan for the Hellenic economy, our methodology detected a contagion effect stemming from Italy, Spain, and Portugal, while intuitively one could have imagined this phenomenon coming solely from the Greek sovereign market. Finally, the analysis of the synchronization and intensity variables provides evidence of a « multi-speed Economic and Monetary Union », refuting the notion of uniform integration of the euro area sovereign bond markets. We believe that it is necessary to complete the institutional architecture of the Economic and Monetary Union to make it more resilient to shocks.